ANALISIS FAKTOR KOMPETENSI, PENGETAHUAN DAN PENGALAMAN KERJA PEGAWAI DAMPAKNYA TERHADAP KINERJA Studi Kasus Pegawai Disdikbud Kabupaten Bireuen - Win, Muslim (IndOmera, 2022)
This study aims to analysis and examine, the influence of competence, knowledge and work experience simultaneously on the performance of the education office employee, Youth and Sports of Bireuen Regency. The type of research used is quantitative research and the research method used is associative method using path analysis. Based on the results of research and discussion of the problems studied, it was found that: 1). The competencies possessed by the employees of the Bireuen Regency Education, Youth and Sports Office, both from the aspects of Knowledge, Skills, Motives, Nature, and Self Image. Influence on employee performance, with a large effect of 20.26%. 2). Knowledge of employees, related to education, experience and interests. significant effect on employee performance, which is calculated from this study is quite significant, namely 17.29%. 3). The work experience factor of employees at the Office of Education, Youth and Sports of Bireuen Regency has only reached 70.04%, not maximal. It is considered that the experience of employees has not fully supported the performance of employees. The results of statistical tests indicate that the work experience variable has an effect on the performance of the Office of Education, Youth and Sports employees - Bireuen Regency, which is 13.93%. The results also revealed that the competence variable, supported by the knowledge and work experience of employees, had an effect on employee performance at the Education, Youth and Sports Office of Bireuen Regency by 54.6%.